CD4-Induced T-20 Binding to Human Immunodeficiency Virus Type 1 gp120 Blocks Interaction with the CXCR4 Coreceptor - Yuan, Wen (American Society for Microbiology, 2004)
The synthetic peptide T-20, which corresponds to a sequence within the C-terminal heptad repeat region (HR2) of the human immunodeficiency virus type 1 (HIV-1) gp41 envelope glycoprotein, potently inhibits viral membrane fusion and entry. Although T-20 is thought to bind the N-terminal heptad repeat region (HR1) of gp41 and interfere with gp41 conformational changes required for membrane fusion, coreceptor specificity determined by the V3 loop of gp120 strongly influences the sensitivity of HIV-1 variants to T-20. Here, we show that T-20 binds to the gp120 glycoproteins of HIV-1 isolates that utilize CXCR4 as a coreceptor in a manner determined by the sequences of the gp120 V3 loop. T-20 binding to gp120 was enhanced in the presence of soluble CD4. Analysis of T-20 binding to gp120 mutants with variable loop deletions and the reciprocal competition of T-20 and particular anti-gp120 antibodies suggested that T-20 interacts with a gp120 region near the base of the V3 loop. Consistent with the involvement of this region in coreceptor binding, T-20 was able to block the interaction of gp120-CD4 complexes with the CXCR4 coreceptor. These results help to explain the increased sensitivity of CXCR4-specific HIV-1 isolates to the T-20 peptide. Interactions between the gp41 HR2 region and coreceptor-binding regions of gp120 may also play a role in the function of the HIV-1 envelope glycoproteins.